2021
DOI: 10.3390/ijerph18010319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Tobacco Smoke on Children’s Anxiety and Behavior in Dental Clinics, Jeddah, Saudi Arabia: A Cross-Sectional Study

Abstract: Background: Environmental tobacco smoke (ETS) has been linked to behavioral problems, but no study has assessed its relationship with dental anxiety. Therefore, this study’s goal is to assess the relation between ETS and both behavioral problems and dental anxiety among children. Methods: The study sample was collected from two centres in Jeddah from October 2019 to January 2020. Inclusion criteria included healthy 5–16-year-old children having their first dental visit with no emergency complaint. The question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Our findings highlight the significance of reinforcing tobacco control in LMICs, where tobacco companies are gradually expanding their markets to LMICs 9 . Accumulating evidence has shown that parental smoking or SHS exposure is associated with adverse health outcomes in children 23–25 . Therefore, the health departments in LMIC ought to integrate tobacco control practices with other child health promotion policies.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our findings highlight the significance of reinforcing tobacco control in LMICs, where tobacco companies are gradually expanding their markets to LMICs 9 . Accumulating evidence has shown that parental smoking or SHS exposure is associated with adverse health outcomes in children 23–25 . Therefore, the health departments in LMIC ought to integrate tobacco control practices with other child health promotion policies.…”
Section: Discussionmentioning
confidence: 73%
“…Accumulating evidence has shown that parental smoking or SHS exposure is associated with adverse health outcomes in children. [23][24][25] Therefore, the health departments in LMIC ought to integrate tobacco control practices with other child health promotion policies. Children are regarded as the core of SDGs, and reducing tobacco use would play a crucial part in global efforts to achieve the SDG 3 (Good Health and Well-Being) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings revealed that students need to avoid using electronic devices to escape from the issue of anxiety [27]. The authors in [28] used ACDAS and FBRS and explored the relationship between environmental tobacco exposure and anxiety among 500 children aged 15 to one year [28]. The authors found a significant association between childhood environmental tobacco disclosure and anxiety among children with a p-value of 0.002 [28].…”
Section: Prevalence and Risk Factors Of Anxiety Among Children: A Rev...mentioning
confidence: 99%
“…The authors in [28] used ACDAS and FBRS and explored the relationship between environmental tobacco exposure and anxiety among 500 children aged 15 to one year [28]. The authors found a significant association between childhood environmental tobacco disclosure and anxiety among children with a p-value of 0.002 [28]. In contrast, a study conducted in Qatar [29] demonstrated a low prevalence of anxiety among children with autism and they did not find any significant differences (p-value≥0.05) between children (n=250) with and without autism.…”
Section: Prevalence and Risk Factors Of Anxiety Among Children: A Rev...mentioning
confidence: 99%